Sustainable management of private and communal lands in northern Ethiopia - Gebremedhin, Berhanu; Swinton, S.M. (CAB International, 2002)
In this chapter, results of recent research conducted in the northern Ethiopian region of Tigray, which has experienced severe land degradation are synthesized. This paper highlights the technological and institutional factors determining the adoption of natural resource conservation at both the household and the community levels. Using 1995/96 data from 250 Tigray farm household interviews, the paper first examines private land management focusing on perception of soil erosion and its yield impact, profitability of soil conservation: the case of stone terraces and determinants of investment of soil conservation: the value of secure land tenure. Using 1998/99 data from a survey of 100 Tigray villages, the paper next investigates the management of communal lands (grazing lands and wood lots), emphasizing on engagement of the communities in collective natural resources (NRM) and effectiveness of collective NRM.